2010
DOI: 10.1501/egifak_0000001205
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the Training Program in Improving Mother Child Relationship through Play

Abstract: ABSTRACT. This study aims to examine the effects of the "Training Program in Improving Mother Child Relationship through Play" on the interaction between mothers and their 4-5 year old children. It is an experimental study based on the pretest, post-test, follow-up test model with experimental, placebo and control groups. The study was conducted with the voluntary participation of upper socio-economic level mothers. Data were obtained by using the Parent Child Relationship Scale, written excerpts in which moth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
1
4
0
3
Order By: Relevance
“…Similarly, Fewell and Deutscher (2004) accounted for positive characteristics in mother-child interaction with the factors of sensitivity to the child's emotional state and interests. Certain studies account for positive characteristics in motherchild interaction with the themes of assistance (Bakkaloğlu and Sucuoğlu, 2000), sensitivityresponsivity (Ceyhun et al, 2015), sensitivity to the emotional state of the child, sensitivity to the child's interests (Mahoney et al, 1986), and asking descriptive questions, praise, and verbal reflection (Akgün and Yeşilyaprak, 2011). Similar to this conclusion of the present study, Leerkes and Crockenberg (2002) identified a positive and significant correlation between the mothers' parenting self-efficacy and sensitivity.…”
Section: Discussion Conclusion and Recommendationssupporting
confidence: 83%
See 2 more Smart Citations
“…Similarly, Fewell and Deutscher (2004) accounted for positive characteristics in mother-child interaction with the factors of sensitivity to the child's emotional state and interests. Certain studies account for positive characteristics in motherchild interaction with the themes of assistance (Bakkaloğlu and Sucuoğlu, 2000), sensitivityresponsivity (Ceyhun et al, 2015), sensitivity to the emotional state of the child, sensitivity to the child's interests (Mahoney et al, 1986), and asking descriptive questions, praise, and verbal reflection (Akgün and Yeşilyaprak, 2011). Similar to this conclusion of the present study, Leerkes and Crockenberg (2002) identified a positive and significant correlation between the mothers' parenting self-efficacy and sensitivity.…”
Section: Discussion Conclusion and Recommendationssupporting
confidence: 83%
“…The steps taken to encode the qualitative data firstly entailed the author watching all video recordings twice followed by the decoding and transcription of the video recordings. Once all video recordings had been transcribed, the transcripts were studied to identify certain codes in line with the literature on mother-child interaction (Mash et al, 1983;Cielinski et al, 1995;Bakkaloğlu & Sucuoğlu, 2000;Diken et, al., 2009;Akgün & Yeşilyaprak, 2011;Ceyhun et al, 2015). The codes thus identified were taken as a reference for a second reading of the records (reinforced with a second viewing of the video recordings as necessary), whereby a list of codes was created with the addition of new codes identified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yeşilyaprak ve Akgün (2010) araştırmalarında, Anne Çocuk İlişkisini Oyunla Geliştirme eğitim programının etkililiğinin 4-5 yaş arasında çocuğu olan annelerin çocuk-ları ile ilişki düzeyi üzerindeki etkisini incelemişlerdir. Bu çalışma deney, plasebo ve kontrol gruplu ön-test, son-test ve izleme modeline dayalı deneysel bir çalışmadır.…”
Section: Etkinliğini Gösteren Araştırmalarunclassified
“…The impact of this relationship has been intriguing to researchers, because parents have an important place in the lives of children, and the mother, as the usual primary caregiver, plays a more important role than the father in bringing up children (Akgiin & Ye §ilyaprak, 2010). Moreover, the mother and daughter usually have a strong connection and greater intimacy than any other adult/parent/child relationships (Thompson & Walker, 1982;Troll & Fingerman, 1996).…”
Section: Background Informationmentioning
confidence: 99%